Deflection of flexural reinforced concrete structures with external non-metallic reinforcement (experimental and theoretical investigation) - Valivonis, Juozas (Journal of Civil Engineering and Management, 2002)
In many cases concrete structures with prestressed steel being sufficiently strong do not meet requirements for stiffness. It is possible to avoid steel prestressing in concrete structures by means of providing additional non-metallic reinforcement, which gives opportunity to increase stiffness of beams significantly. Experimental investigations of reinforced concrete beams with external non-metallic reinforcement were made. Method for calculation of deflection of beams with external non-metallic reinforcement is presented in this article. Theoretical calculations of deflections using the proposed method were performed. Sufficiently good agreement with experimental deflection values was obtained.Frist Published Online: 30 Jul 2012